Different Flooding Conditions Affected Microbial Diversity in Riparian Zone of Huihe Wetland - Bademu Qiqige; Jingjing Liu; Ming Li; Xiaosheng Hu; Weiwei Guo; Ping Wang; Yi Ding; Qiuying Zhi; Yuxuan Wu; Xiao Guan; Junsheng Li (Microorganisms)
The soil microbiome plays an important role in wetland ecosystem services and functions. However, the impact of soil hydrological conditions on wetland microorganisms is not well understood. This study investigated the effects of wetted state (WS); wetting–drying state (WDS); and dried state (DS) on the diversity of soil bacteria, fungi, and archaea. The Shannon index of bacterial diversity was not significantly different in various flooding conditions (p > 0.05), however, fungal diversity and archaeal communities were significantly different in different flooding conditions (p < 0.05). Significant differences were found in the beta diversity of bacterial, fungal, and archaeal communities (p < 0.05). Additionally, the composition of bacteria, fungi, and archaea varied. Bacteria were predominantly composed of Proteobacteria and Actinobacteria, fungi mainly consisted of Ascomycota and Mucoromycota, and archaea were primarily represented by Crenarchaeota and Euryarchaeota. Bacteria exhibited correlations with vegetation coverage, fungi with plant diversity, and archaea with aboveground vegetation biomass. The pH influenced bacterial and archaeal communities, while soil bulk density, moisture, soil carbon, soil nitrogen, and plant community diversity impacted fungal communities. This study provides a scientific basis for understanding the effects of different hydrological conditions on microbial communities in the Huihe Nature Reserve; highlighting their relationship with vegetation and soil properties, and offers insights for the ecological protection of the Huihe wetland.